Preparation of Optically Active Alkoxy-serines from Amino-amide Racemate Catalyzed by Escherichia coli Cells with Peptidase B Activity - Wang, Zhi-yuan; Liu, Jun-zhong; Xu, Li-sheng; Zhang, Hong-juan; Liu, Qian; Jiao, Qing-cai (Chemical research in Chinese universities, 2013)
Alkoxy-L-serines are useful for peptide syntheses. The demand for alkoxy-L-serines in the pharmaceutical industries continues to increase because of their multiple physiological effects. In this research, an improved method for alkoxy-L-serines synthesis is reported. A series of substrates, DL-fl-alkoxy-a-amino propionamides, was used for the synthesis of alkoxy-serines catalyzed by Escherichia coli cells with peptidase B（PepB） activity. The results show that PepB has a high resolution activity with DL-fl-alkoxy-a-amino propionamides as substrate. Reaction conditions were optimized, i.e., DL-β-methoxy-a-amino propionamide as substrate at pH=9.0, 40 ℃ and 14 h, and the optimal reaction concentration is 400 mmol/L. The results also show that divalent metal cations exhibit different effects on the PepB activity, for example, Zn2＋ and Cu2＋ can obviously inhibit the activity of PepB, whereas Co2＋, Ca2＋, Mn〉 and Mg2＋ at low concentrations can activate PepB. This research provides access to enantiomerically enriched and valuable alkoxy-L-serines from a simple amino-amide racemate.